Prescribing practices for malaria in a rural Ugandan hospital: evaluation of a new malaria treatment policy - Ucakacon, P. S; Achan, J.; Kutyabami, P.; Odoi, A. R.; Kalyango, N. J. (African Health Sciences, 2011)
Increasing resistance to first line antimalarial drugs led to a change in the antimalarial policy of Uganda in 2005. Successful implementation of this policy depends on changing prescribing patterns of health workers. Objectives: To describe prescribing patterns for malaria and associated factors in a rural Ugandan hospital following a change in antimalarial treatment policy from chloroquine plus sulphadoxine-pyrimethamine to artemisinin-based combination therapies. Methods: From the outpatients register, 715 prescriptions for malaria were reviewed. Data was collected on patient demographics, prescriber factors and prescription patterns. Prescriptions were considered to conform to the new antimalarial policy if artemether-lumefantrine was prescribed for uncomplicated malaria or quinine for treatment failure or complicated malaria. Results: The most frequently prescribed antimalarials for uncomplicated and complicated malaria were artemetherlumefantrine (n=564, 88.5%) and quinine (n=66, 84.6%) respectively. The proportion of prescriptions conforming to the new antimalarial treatment policy was 88.1% (n=630). Predictors of conformity were: duration in service of less than 6 years (OR=3.40. CI=1.24-9.33), prescriber’s profession (OR=97.51, CI=27.29-348.34) and diagnosis of uncomplicated malaria (OR=10.13, CI=3.37-30.42). Conclusions: Adequate training and provision of information relevant to the needs of different cadres of health workers is needed to promote effective uptake of new treatment policies.
Keywords: Malaria policy; Prescribing practices; Malaria treatment